El inglés como una herramienta evangelizadora en las escuelas de Kerala: Un análisis diacrónico sobre el elitismo anglófono a través de «Indulekha» (1889) de O. Chandu Menon y «El Dios de las Pequeñas Cosas» (1997) de Arundhati Roy (Castilla. Estudios de Literatura, 2025)
This manuscript investigates the factors contributing to Kerala’s superior educational performance, particularly in English language instruction, compared to the rest of India. It examines two distinct educational models: the colonial governmental approach articulated in Macaulay's Minute on Education (1835) and the missionary pedagogy exemplified in the works of Rev. Samuel Mateer. A period-over-period analysis explores the lasting cultural implications of these British-centered models, highlighting their impact on Kerala’s educational framework. To illustrate these effects, a comparative analysis of literary works, Indulekha (1889) and The God of Small Things (1997), is undertaken, emphasizing themes of cultural accommodation and colonial legacy.
Keywords: adquisición del inglés; educación colonial; escuelas misioneras; Kerala; literatura poscolonial